Impact Of Academic Information Systems And Teachers' Competitions On The Deposition Of School Students In Science Administration Banten - Saripan, Saripan; Rizal Bahtiar (Sean Institute, 2024)
The study aims to find out the impact of academic information systems on student satisfaction at the Banten College of Administrative Sciences, to know the influence of faculty competence on students’ satisfaction in the Bante College of Administration Sciences and to know how the academic informatics system and the faculty’s competence jointly influence student’s satisfaction. According to Hansemark and Albinsson (2004) quoted Singh (2006), “General customer satisfaction is an attitude towards a service provider, or an emotional reaction to the difference between what a customer expects and what they receive, regarding the fulfilment of a need for a purpose or desire.” The method used in this study was a quantitative method through a questionnaire, with a population of 902 active students at the Banten College of Administrative Sciences and a sample of 86 people, sample calculations using Isaac and Michael's formulas. Based on analysis with the help of the application SPSS version 24 showed that the impact of the academic information system on student satisfaction of Banten College of Administrative Sciences was 25.4%, the influence of the faculty competence on the students satisfaction at Banten School of Administration Sciences of 17.5%, and the effect of the educational information system and the competence of the lecturer jointly on the Student Satisfaction at the Banten High School of administrative sciences, was 47.9%.